Comparative Analysis and Accuracy Assessments of Terrain Heights Determination Towards Effective and Accurate Heights Measurements in Construction Works - Qaadri, J. A.; Alagbe, A. O.; Olaosegba, S. O.; Okegbola, M. O.; Ajisafe, B. I. (Journal of Spatial Information Sciences, 2025)
Engineering and construction works require precise height or elevation determination, and providing such essential information is in the purview of geomatics engineers. Oftentimes, civil engineers are less concerned and mostly oblivious of the choice of method employed in the acquisition of such data but are more particular about the accuracy, time limitation and cost implication whereas, some of such engineering and construction works may require lesser accuracy. This study therefore attempts a comparative analysis and accuracy assessment of height determination by trigonometric heighting, stadia and tangential tacheometric methods relative to reference data acquired by spirit levelling operation. Thirty fixed points were selected and their elevations were determined using the afore-mentioned methods. Statistical analytical tools were employed for the comparative analytical process. The results analysis indicates that the three (3) methods –– trigonometric heighting, stadia and tangential tacheometric methods –– gave 0.077, 0.172 and 0.117 standard deviations and 0.017, 0.038, and 0.029 RMSE respectively. Thus, it can be inferred that Trigonometric heighting is more accurate relative to the other two (2) methods. However, a one-way ANOVA test shows P-value of 0.1102 as against F-Critical value of 3.1013. This reveals that there is no significant difference in the mean of the heights obtained by the three methods. Hence, the major mitigating factors which should influence the choice of any of the three (3) methods are time limitation and cost implication but not necessarily accuracy.